CHEMISTRY TEACHERS’ PEDAGOGICAL CONTENT KNOWLEDGE IN TEACHING LEWIS STRUCTURE - Mashfufatul Ilmah; Fatayah (Universitas Negeri Surabaya, 2026)
Lewis structures remain a challenge in chemistry teaching. Many studies have examined students' misconceptions about Lewis structures, but studies specifically analyzing how teachers' Pedagogical Content Knowledge (PCK) influences teaching practices on this topic are still limited. This study aims to analyze chemistry teachers' PCK on the topic of Lewis Structures by examining its three components, Content Knowledge (CK), Student of Knowledge (KS), and Pedagogical Knowledge (PK), and see the relationship between the three. This study uses a qualitative descriptive approach, involving 5 chemistry teachers in the Cilegon area. Data were collected through conceptual understanding test, semi-structured interviews, and an analysis of teachers’ lesson plan documents. Data validity was ensured through triangulation of sources and data collection techniques. Data were analyzed through data reduction, data display, and conclusion drawing. The results of the study showed that although 80% of teachers were able to distinguish Lewis symbols and Lewis structures, 40% of teachers had misconceptions about the octet rule, only 20% were able to calculate formal charges correctly, and all teachers had difficulty achieving resonance with atomic charge distribution. This limitation of Content Knowledge (CK) has an impact on the low ability of teachers to identify student misconceptions (KS) as well as on learning strategies that tend to be procedural and lecture-centered (PK). These findings indicate that the interaction between CK, KS, and PK determines the quality of teachers' PCK and emphasizes the importance of strengthening conceptual CK in the professional development of chemistry teachers.